Independent female filmmakers a chronicle through interviews, profiles, and manifestos - Meek, Michele (Routledge, 2019)
Independent Female Filmmakers collects original and previously published essays, interviews, and manifestos from some of the most defining and groundbreaking independent female filmmakers of the last 40 years. Featuring material from the seminal magazine The Independent Film and Video Monthly--a leading publication for independent filmmakers for several decades--as well as new interviews conducted with the filmmakers, this book, edited by Michele Meek, presents a unique perspective into the ethnically and culturally diverse voices of women filmmakers whose films span narrative, documentary, and experimental genres and whose work remains integral to independent film history from the 1970s to the present. Independent Female Filmmakers also includes a biographical profile of each filmmaker, as well as an online resource with links to additonal interviews and a sample course syllabus. The filmmakers in this book include: Lisa Cholodenko (High Art, The Kids Are All Right), Martha Coolidge (Valley Girl, Real Genius, Introducing Dorothy Dandridge), Cheryl Dunye (The Watermelon Woman, Stranger Inside), Miranda July (The Future, Me And You And Everyone We Know), Barbara Kopple (Harlan County USA, Wild Man Blues), Maria Maggenti (The Incredibly True Adventures of Two Girls in Love), Deepa Mehta (Fire, Earth, Water), Trinh T. Minh-ha (Surname Viet, Given Name Nam, Night Passage) . . . and more!